2023
DOI: 10.1097/cm9.0000000000002711
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between mucus layer and gut microbiota in non-alcoholic fatty liver disease: Soil and seeds

Abstract: The intestinal mucus layer is a barrier that separates intestinal contents and epithelial cells, as well as acts as the "mucus layersoil" for intestinal flora adhesion and colonization. Its structural and functional integrity is crucial to human health. Intestinal mucus is regulated by factors such as diet, living habits, hormones, neurotransmitters, cytokines, and intestinal flora. The mucus layer's thickness, viscosity, porosity, growth rate, and glycosylation status affect the structure of the gut flora col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…The gut microbiota performs complex metabolic activities, generating various metabolites that can have both harmful and beneficial effects [57,58]. These metabolites play a significant role in the interactions between colorectal cancer cells and the gut microbiota.…”
Section: Et Almentioning
confidence: 99%
“…The gut microbiota performs complex metabolic activities, generating various metabolites that can have both harmful and beneficial effects [57,58]. These metabolites play a significant role in the interactions between colorectal cancer cells and the gut microbiota.…”
Section: Et Almentioning
confidence: 99%
“…The study by You et al (2023) further demonstrated that a metabolite called N-acetyl-D-glucosamine (GlcNAc), induced by B. vulgatus , had a mucin-stimulating effect, effectively reversing the decline of Akkermansia in mice fed a HFD. Additionally, B. vulgatus serves as a provider of nutrients, supplying microbiota-accessible carbohydrates, such as mucin glycans, to maintain microbial homeostasis, particularly with Lactobacilli and Bifidobacteria , which play a crucial role in the mucus integrity, indirectly reinforcing the cooperative network with Akkermansia ( You et al, 2023 ; Zhang et al, 2023 ). Therefore, it can be inferred that the therapeutic effects of Bacteroides in NAFLD are partially mediated by increasing the abundance of beneficial flora in the gut.…”
Section: Introductionmentioning
confidence: 99%